Effect of Land Use Systems on Distribution of Soil Macronutrients of Lesser Himalayas, India - Fozia Shafiq Wani; Farida Akhter; Shakeel Mir; Zahoor Ahmed Baba; Showkat Maqbool (Journal of the Indian Society of Soil Science, 2023)
The present study was carried out to evaluate the effect of land use systems on available macronutrients in north Kashmir of lesser Himalayan region. Composite soil samples using purposive sampling method were taken from major land use systems viz. (A) Forestry (B) i) Horticulture (Vegetables) ii) Horticulture (Fruits) (C) Agriculture (D) Agri-Horti (E) Pasture prevailing in the study area. The soil texture among different land use systems varied from silt, silt loam, clay loam and silty clay loam. The pH varied from moderately acidic to neutral under examined land use systems. The electrical conductivity (EC) values were less than 0.8 dS m-1 indicating no salinity hazards. The soil organic carbon (SOC) was found highest under forests and lowest under agriculture. The cation exchange capacity (CEC) of soils followed the order forestry > pasture > horticulture (vegetables) > horticulture (fruits) > agri-horti > agriculture which was almost similar in trend to that of OC. The macronutrients showed wide variation among different land use systems with nitrogen (N) and phosphorus (P) content highest under forestry and lowest under agri-horti, potassium (K) ranged from medium to high under all land use systems. Sulphur (S) showed highest value under forestry and lowest value under horticulture. Exchangeable cations (calcium and magnesium) showed highest value under pasture soils and lowest value under agriculture. The pH and EC showed a negative significant correlation with N, P, S and positive significant correlation with Ca and Mg. Organic carbon showed a positive correlation with all nutrients. The CEC showed a positive significant correlation with N, P, K, S, Ca and Mg. Hence, it is established that natural ecosystems such as forests accumulated higher soil OC than artificial ecosystems, thus emphasizing the significance of forest as pre-eminent managed ecosystems and any shift from the ecological equilibrium and land use change due to human activities has an impact on soil health across the land use systems in this zone.